Estimating global geographical distribution and ecological niche dynamics of Ammannia coccinea under climate change based on Biomod2 - YanJing Zhang; Jie Hu; ChenBin Wang; YaQiong Wan; MuLan Ji; FangZhou Ma; YiQing Lu (Scientific Reports)
Abstract Invasive alien plants pose a significant threat to biodiversity and the agricultural economy. The invasive weed (Ammannia coccinea) competes with rice in paddy fields, potentially threatening rice production. Despite the crucial need to estimate the global geographical distribution and ecological niche dynamics of A. coccinea for effective early warning, control strategies, and global rice security, relevant research remains scarce. This study utilized the Biomod2 platform, which integrates multiple single models into ensemble model, incorporating environmental and species data to analyze the distribution range shifts of A. coccinea under current and future climate scenarios. It also quantified and analyzed shifts in the species’ ecological niche across these climate scenarios. The results indicated that the potential suitable areas for A. coccinea were mainly in Southern North America, northern and south-eastern South America, south-western Europe, the Middle East, central Africa, western Asia, south-eastern Asia, with a gradual increase in mid-high suitability habitat over time and radiation levels. While the overall ecological niche of A. coccinea remains stable, minor shifts are expected under future conditions. Temperature, precipitation, and the human impact index were the key factors influencing the future distribution of A. coccinea. Climate change contributes to the expansion of A. coccinea's highly suitable areas and shifts its ecological niche. Organizations efforts should focus on preventing the spread of A. coccinea in regions where its potential distribution overlaps with key rice production areas. The findings of this study provide critical insights into the global distribution and ecological niche dynamics of A. coccinea, aiding in the development of early warning and control strategies to mitigate its impact on biodiversity, agriculture, and particularly rice production under future climate scenarios.